Gastrodia elata Blume Polysaccharides Attenuate Vincristine-Evoked Neuropathic Pain through the Inhibition of Neuroinflammation - Hengtao Xie; Yingying Chen; Wei Wu; Xiaobo Feng; Kairong Du (Mediators of Inflammation)
Vincristine (Vin) is a well-known antitumor agent that frequently evokes neuropathic pain and decreases the quality of life of patients. Polysaccharides (GBP) extracted from Gastrodia elata Blume have been demonstrated to possess anti-inflammatory and neuroprotective effects in vivo; however, the effects of GBP on Vin-induced neuropathic pain remain unknown. The present study is aimed at exploring the alleviative potential of GBP against chemotherapy-evoked peripheral neuropathy to better understand and extend its pharmacological application. Vin was administered intraperitoneally to evoke neuropathic pain. GBP was orally administered for 21 days. The mechanical allodynia and thermal hyperalgesia were assessed using the Von Frey test and hot-plate test. Histopathological changes were assessed by hematoxylin and eosin staining. ELISA kits were used to measure the levels of inflammatory cytokines in the sciatic nerve, spinal cord, and dorsal root ganglion (DRG). qRT-PCR was employed to examine the expression of inflammatory cytokines and Sirtuin1 (SIRT1) in the sciatic nerve, spinal cord, and DRG. Our findings revealed that GBP treatment enhanced the paw withdrawal latency and paw withdrawal threshold and restored Vin-induced sciatic nerve damage in rats. GBP also attenuated the Vin-induced increase of proinflammatory cytokine levels, including IL-6, IL-8, TNF-α, IL-1β, and NF-κB. On the molecular level, treatment with GBP downregulated the mRNA levels of IL-6, IL-8, TNF-α, and IL-1β in the sciatic nerve, spinal cord, and DRG. Meanwhile, GBP increased SIRT1 activity and mRNA expression levels. Our data indicated that GBP exerted a potential protective effect against chemotherapy-induced neuropathic pain which might be mediated via the inhibition of neuroinflammation.